The Influence of Flipped Based Learning on Students' Social Thinking Skills at Muhammadiyah Schools - Samsul Huda; Chusnul Muali (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The increasing emphasis on 21st-century competencies has highlighted the critical need for instructional approaches that extend beyond cognitive achievement to include the development of students’ social thinking skills. Despite this demand, conventional teacher-centered practices continue to restrict meaningful interaction, limiting students’ ability to develop essential social competencies. This study investigates the effect of flipped-based learning on students’ social thinking skills in elementary education. A quasi-experimental design with a pretest–posttest non-equivalent control group was employed, involving 64 sixth-grade students divided into experimental and control groups. Data were collected using a validated Likert-scale questionnaire and scenario-based tasks measuring five dimensions: social awareness, cooperation, empathy, interpersonal communication, and social problem-solving. The data were analyzed using Multivariate Analysis of Covariance, followed by univariate ANCOVA and paired t-tests. The results indicate a statistically significant and substantial effect of flipped-based learning across all dimensions of social thinking skills (Wilks’ Lambda = 0.154, p < 0.001). The experimental group demonstrated a markedly higher improvement (14.38%) compared to the control group (4.92%), with large effect sizes observed in cooperation, interpersonal communication, and social problem-solving. These findings suggest that flipped-based learning fosters an interactive learning environment that enhances students’ social reasoning and collaborative capacities. This study contributes theoretically by extending flipped learning research into the social domain and integrating social constructivist and social cognitive perspectives. Practically, it provides a robust framework for designing student-centered learning environments that support holistic development. Overall, flipped-based learning is positioned as a transformative pedagogical model for advancing social thinking skills in contemporary education.